2002
DOI: 10.1128/jb.184.5.1234-1243.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Flavoprotein MrsD Catalyzes the Oxidative Decarboxylation Reaction Involved in Formation of the Peptidoglycan Biosynthesis Inhibitor Mersacidin

Abstract: The lantibiotic mersacidin inhibits peptidoglycan biosynthesis by binding to the peptidoglycan precursor lipid II. Mersacidin contains an unsaturated thioether bridge, which is proposed to be synthesized by posttranslational modifications of threonine residue ؉15 and the COOH-terminal cysteine residue of the mersacidin precursor peptide MrsA. We show that the flavoprotein MrsD catalyzes the oxidative decarboxylation of the COOH-terminal cysteine residue of MrsA to an aminoenethiol residue. MrsD belongs to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 38 publications
2
89
0
1
Order By: Relevance
“…Thus, we postulate that homocysteine acts as a source of sulfur atoms for TDA. In support of this, the essential tdaF gene most probably encodes a homo-oligomeric flavin-containing cysteine decarboxylase, which catalyzes the oxidative decarboxylation of cysteine residues for several substrates (Majer et al, 2002). Therefore, TdaF could provide a reactive, sulfur-containing precursor for the final steps of TDA synthesis (Figure 6).…”
Section: Tda Biosynthesis In P Gallaeciensis Dsm 17395mentioning
confidence: 99%
“…Thus, we postulate that homocysteine acts as a source of sulfur atoms for TDA. In support of this, the essential tdaF gene most probably encodes a homo-oligomeric flavin-containing cysteine decarboxylase, which catalyzes the oxidative decarboxylation of cysteine residues for several substrates (Majer et al, 2002). Therefore, TdaF could provide a reactive, sulfur-containing precursor for the final steps of TDA synthesis (Figure 6).…”
Section: Tda Biosynthesis In P Gallaeciensis Dsm 17395mentioning
confidence: 99%
“…The gene encoding this type of enzyme is also found in the gene clusters of epidermin and mersacidin. The modifications made by the flavoproteins are required for full activity of these peptides (24,29). Whereas NisT displays rather broad transport specificity of peptides fused to the leader peptide of nisin, NisP has been shown to process only fully modified prenisin (19).…”
Section: Resultsmentioning
confidence: 99%
“…A FAD-dependent flavoprotein catalyzes this reaction for mersacidin, a lantibiotic produced by Bacillus sp. (29). Another flavoprotein, which is flavin mononucleotide (FMN) dependent, catalyzes the same reaction for epidermin, a lantibiotic of S. epidermidis, and this enzyme is essential for formation of a biologically activity peptide (24).…”
Section: Discussionmentioning
confidence: 99%
“…Although several active site residues of eubacterial and eukaryotic CoaC activities are not conserved in Methanocaldococcus Dfp (12), we were able to demonstrate its PPC decarboxylase activity. Furthermore, it is shown that HisCoaC (and thus Dfp) forms homododecamers like the E. coli Dfp protein and the related peptidyl-cysteine decarboxylases EpiD and MrsD (7,10,13). We show that M. jannaschii CoaB is a CTP-dependent enzyme, although the nucleotide binding motif II contains a Lys residue, which is characteristic for the ATP-dependent PPC synthetases (5).…”
mentioning
confidence: 99%